An Evolutionary-Based Framework for Analyzing Mold and Dampness-Associated Symptoms in DMHS - Daschner, Alvaro (Frontiers in Immunology, 2017)
Among potential environmental harmful factors, fungi deserve special consideration. Their intrinsic ability to actively germinate or infect host tissues might determine a prominent trigger in host defense mechanisms. With the appearance of fungi in evolutionary history, other organisms had to evolve strategies to recognize and cope with them. Existing controversies around dampness and mold hypersensitivity syndrome (DMHS) can be due to the great variability of clinical symptoms but also of possible eliciting factors associated with mold and dampness. An hypothesis is presented, where an evolutionary analysis of the different response patterns seen in DMHS is able to explain the existing variability of disease patterns. Classical interpretation of immune responses and symptoms are addressed within the field of pathophysiology. The presented evolutionary analysis seeks for the ultimate causes of the vast array of symptoms in DMHS. Symptoms can be interpreted as induced by direct (toxic) actions of spores, mycotoxins, or other fungal metabolites, or on the other side by the host-initiated response, which aims to counterbalance and fight off potentially deleterious effects or fungal infection. Further, individual susceptibility of immune reactions can confer an exaggerated response, and magnified symptoms are then explained in terms of immunopathology. IgE-mediated allergy fits well in this scenario, where individuals with an atopic predisposition suffer from an exaggerated response to mold exposure, but studies addressing why such responses have evolved and if they could be advantageous are scarce. Human history is plenty of plagues and diseases connected with mold exposure, which could explain vulnerability to mold allergy. Likewise, multiorgan symptoms in DMHS are analyzed for its possible adaptive role not only in the defense of an active infection, but also as evolved mechanisms for avoidance of potentially harmful environments in an evolutionary past or present setting.